2012
DOI: 10.1177/1754073912439761
|View full text |Cite
|
Sign up to set email alerts
|

Is Pain a Human Universal? A Cross-Linguistic and Cross-Cultural Perspective on Pain

Abstract: Pain is a global problem whose social, economic, and psychological costs are immeasurable. It is now seen as the most common reason why people seek medical (including psychiatric) care. But what is pain? This article shows that the discourse of pain tends to suffer from the same problems of ethnocentrism and obscurity as the discourse of emotions in general. Noting that in the case of pain, the costs of miscommunication are particularly high, this article offers a new paradigm for communicating about pain. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…For example, chronic migraine sufferers experience greater activation of systems involved in pain when imagining pain and reading pain-related words (Eck et al, 2011; see also Knost, Flor, Braun, & Birbaumer, 1997;Vukovic et al, 2019;Weiss, Miltner, & Dillmann, 2003), and depressed individuals show enhanced brain activation and memory for pain words (Nikendei, Dengler, Wiedemann, & Pauli, 2005). Cross-cultural differences in pain-language are also important to consider in clinical situations, where miscommunication-e.g., between doctor and patient-could be harmful (Wierzbicka, 2012).…”
Section: Painmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, chronic migraine sufferers experience greater activation of systems involved in pain when imagining pain and reading pain-related words (Eck et al, 2011; see also Knost, Flor, Braun, & Birbaumer, 1997;Vukovic et al, 2019;Weiss, Miltner, & Dillmann, 2003), and depressed individuals show enhanced brain activation and memory for pain words (Nikendei, Dengler, Wiedemann, & Pauli, 2005). Cross-cultural differences in pain-language are also important to consider in clinical situations, where miscommunication-e.g., between doctor and patient-could be harmful (Wierzbicka, 2012).…”
Section: Painmentioning
confidence: 99%
“…More generally, an examination of the lower senses is timely, as there is accumulating evidence for the importance of these senses in all our lives. We rely on the language of touch to convey our sense of comfort or pain (e.g., Melzack, 1975), and miscommunication can be harmful (Wierzbicka, 2012). Taste and smell are crucially intertwined with our consumption of food and drinks, which has important implications for our health (Boesveldt & de Graaf, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linguistic research has the potential to show which features of pain are artefacts of the English language, and which are universal and might in turn be taken to be philosophically significant (Wierzbicka 2012). Mandarin Chinese is the world's most widely spoken native tongue (Wang and Sun 2015: 578), and so makes an excellent test case.…”
mentioning
confidence: 99%
“…This has highlighted the fact that the Vietnamese patients did not particularly favour emphasising the impacting sense of pain by using the modal verb bị. Wierzbicka (2012) claimed that most languages in the world have counterparts for the pain expression it hurts, functioning to both express and describe one's feeling. The double function of pain language has been confirmed in Lascaratou's (2007Lascaratou's ( , 2008 When investigating pain as process in English and Greek, Halliday (1998) and Lascaratou (2007) did not present the semantic aspects of pain.…”
Section: Concluding Remarks About Pain As Process In Vietnamesementioning
confidence: 99%
“…The other 60% of the descriptors in the sensory and sensory-miscellaneous categories were retained because they were "used frequently and unambiguously in the communication of pain" (Fernandez & Towery, 1996, p. 36). In addition, in her discussion about cross-linguistic and crosscultural perspective on pain, Wierzbicka (2012) (Costa et al, 2009). It was found that most of the adaptations had not been subject to adequate clinical testing, and few authors followed the accepted guidelines for cross-cultural adaptation.…”
mentioning
confidence: 99%